2022
DOI: 10.1186/s13063-022-06328-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of neostigmine and sugammadex on postoperative residual curarization and postoperative pulmonary complications by means of diaphragm and lung ultrasonography: a study protocol for prospective double-blind randomized controlled trial

Abstract: Background Postoperative residual curarization (PORC) may be a potential risk factor of postoperative pulmonary complications (PPCs), and both of them will lead to adverse consequences on surgical patient recovery. The train-of-four ratio (TOFr) which is detected by acceleromyography of the adductor pollicis is thought as the gold standard for the measurement of PORC. However, diaphragm function recovery may differ from that of the peripheral muscles. Recent studies suggested that diaphragm ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It has also been suggested that sugammadex is more suitable than neostigmine for restoring diaphragmatic function. However, there are also studies reporting that there is no difference in general between the two decurarization agents (27,28,29,30). According to the results of this meta-analysis, the fact that there was no significant difference between sugammadex and neostigmine in terms of hospital stay time, which is a measure of patient mobilization, is a results against the above information about sugammadex.…”
Section: Discussionmentioning
confidence: 78%
“…It has also been suggested that sugammadex is more suitable than neostigmine for restoring diaphragmatic function. However, there are also studies reporting that there is no difference in general between the two decurarization agents (27,28,29,30). According to the results of this meta-analysis, the fact that there was no significant difference between sugammadex and neostigmine in terms of hospital stay time, which is a measure of patient mobilization, is a results against the above information about sugammadex.…”
Section: Discussionmentioning
confidence: 78%